Recurrent Aphthous Stomatitis (RAS) and exfoliative cheilitis in elderly psoriasis sufferer - Siti H. Nurhasanah; Astrid Palmasari; Dwi Setyaningtyas; Sujati Sujati; Okty Setyawati (DiscoverSys Inc., 2016)
Recurrent Aphthous Stomatitis (RAS) is a disorder in the oral cavity, with a characterized symptom as ulceration, recurrent and very painfull. The etiology is idiopathic, with multifactorial predisposition. Exfoliative cheilitis is a persistent lesion on the lip, with a characterized cracking and desquamative, with crustae and inflammation. An elderly male (72 yrs) suffered with ulcer on his oral cavity, cracking lips and pain on both of his cheeks, skin, since 5 years ago. The pain is recurrent. On the clinical examination, there were some desquamation, both on the skin and vermilion border, whether on the inner lips (labial fold mucosa), there were ulcers with diameter about 1 cm. The laboratory test was within normal limits, except the LED was 40 mm/hour (n:<15). The diagnosis was Recurrent Aphthous Stomatitis (RAS) for the ulcer and Exfoliative cheilitis for the cracking lips. The treatment he received was a gargle liquid, topical corticosteroid and supplement. The skin’s disorder was revered to the skin and genital disease department, for further management. As a dental general practioner, had to be very careful and familiar for every changes that may be occur both in the outer or inner oral cavity. Other disorder that need refferal, had to be done with team work, to the colleague from the right connection.